Early magnetic resonance imaging predicts 12-month outcome in neonates with congenital diaphragmatic hernia - Groteklaes, Anne; Dresbach, Till; Kipfmüller, Florian; Stutte, Sonja; Bagci, Soyhan; Grass, Tamara; Nitsch-Felsecker, Patrizia; Pantazis, Christos; Schmitt, Joachim; Schroeder, Lukas; Mueller, Andreas; de Vries, Linda S.; et al. (Psychological assessment, 2025)
Introduction: Advances in neonatology, neonatal surgery, and extracorporeal membrane oxygenation have improved the prognosis of congenital diaphragmatic hernia (CDH). However, CDH survivors are at considerable risk of long-term neurological morbidity. Magnetic resonance imaging (MRI) abnormalities are reported in up to 84% of CDH survivors but have only been rarely compared with neurodevelopmental outcomes. This study aims to investigate whether assessment of postnatal MRI in CDH survivors allowed association with and prediction of long-term outcome. Methods: Brain MRI was performed in 36 neonates with CDH using the Weeke score, assessing the mammillary bodies, the corpus callosum, cortical folding, and cerebrospinal fluid space (CSF). Outcomes were measured using Bayley-III-examinations at 12 months. Results: In total, 91.6% of the neonates exhibited MRI abnormalities. Among them, 83.3% showed white matter (WM), 16.6% gray matter abnormalities, 8.3% cerebellar abnormalities, and 20% had an intracranial hemorrhage. A total of 30.5% showed abnormal mammillary bodies, 44.4% enlarged CSF, 5.5% reduced cortical folding, and 8.3% reduced corpus callosum thickness. While the use of the Weeke score was not helpful for outcome prediction, specific MRI abnormalities were associated with adverse long-term outcomes. Based on these findings, a novel MRI-scoring system was developed. This easy-to-perform score effectively predicted adverse outcomes at 12 months. Conclusion: Interpretation of MRI in neonates with CDH should focus on WM pathologies, CSF enlargement, internal capsule involvement, mammillary body abnormalities, and intraventricular hemorrhage. Our novel simple scoring system helps identify neonates at risk for adverse neurological outcomes at discharge and aids to implement therapeutic strategies at an early point. While advances in therapy have improved the survival of neonates with congenital diaphragmatic hernia (CDH), there is a high risk of long-term neurodevelopmental problems in neonates with CDH. Early diagnosis of those neonates at risk for neurodevelopmental problems may help start therapeutic strategies at an early point. In this study, we investigated whether early postnatal brain magnetic resonance imaging (MRI) allows to predict long-term neurodevelopmental outcome in neonates with CDH. We analyzed 36 brain MRIs in neonates with CDH and compared them to long-term outcome defined by a neurological examination at 12 months. Most of the neonates with CDH showed abnormal MRI findings, mainly white matter abnormalities, bleedings, and enlarged cerebrospinal fluid space. We developed a specific MRI score which allows to predict neurodevelopmental outcome in neonates with CDH. This easy-to-perform scoring system may help identify neonates at risk for adverse neurodevelopmental outcome and start therapeutic strategies at an early point before they clinically manifest.
Gesehen am 24.11.2025